2014
DOI: 10.5963/phf0301002
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Status among Type (2) Diabetes Mellitus in the State of Qatar

Abstract: The results showed that zinc deficiency is common among type 2 diabetic patients due to hyperglycemia and polyurea. Periodic serum zinc measurement is recommended for type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Our findings are in line with Obeid et al [56] who also demonstrated a risk of Zn deficiency in Lebanese subjects with metabolic syndrome. The low plasma Zn concentrations were also seen in obese individuals, those with hypertension and type 2 diabetes [57,58]. Fe and Cu status data were within the estimated reference ranges for adult population, and similar to the values reported elsewhere [33,59].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are in line with Obeid et al [56] who also demonstrated a risk of Zn deficiency in Lebanese subjects with metabolic syndrome. The low plasma Zn concentrations were also seen in obese individuals, those with hypertension and type 2 diabetes [57,58]. Fe and Cu status data were within the estimated reference ranges for adult population, and similar to the values reported elsewhere [33,59].…”
Section: Discussionsupporting
confidence: 87%
“…Studies of zinc concentration in the human body are scarce, and have shown inconsistent results. Zinc deficiency has been observed in patients in some counties with increased oxidative stress and generation of inflammatory status and the decrease concentrations of this element occur in patients with MS [ 3 ], in patients with type 2 diabetes mellitus [ 6 ] and with hypertension [ 7 ] than in healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…There is not great number of public studies nowadays which examine Zn status in a human organism and present studies show the results that are not congruent (Olechnowicz, 2018). However, the majority of studies show that the Zn deficiency can be seen in states of higher oxidation stress, inflammatory process, in patients with metabolic syndrome, diabetes mellitus type 2 (DM2) and arterial hypertension (HTA) comparing to healthy population (Seo et al, 2014;Daradkeh et al 2014;Marcinek et al, 2015).…”
Section: Introductionmentioning
confidence: 73%